GENETIC RELATIONSHIP BETWEEN TORAJANESE LANGUAGE AND MANDARESE LANGUAGE - Adawiah, Rabiatul; Sari, Desfi Nira (Elite : English and Literature Journal, 2017)
Abstract Some codices state that ancestors of South and West Sulawesi people come from Toraja area. It drives to a logic thinking that Torajanese is protolanguage of other local languages such as Makassarese. Buginese and Mandarese. This research is aimed to investigate the genetic relationship between Torajanese and Mandarese and to identify kinds of sound change happening from Torajanese into Mandarese. The method used in this paper is lexicostatistics by comparing 200 Swadesh basic vocabulary of Torajanese and Mandarese. The result shows that Torajanese and Mandarese can be categorized as two relative languages with kinship percentage rate of 49%. The second finding is that there are eight patterns of sound changes; they are apharesis, syncope, lenition, fortition, assimilitaion, vowel breaking, metathesis and prosthesis. Abstrak Beberapa naskah kuno menyatakan bahwa nenek moyang berbagai suku yang berada di wilayah Sulawesi Selatan dan Sulawesi Barat berasl dari Toraja. Hal tersebut melahirkan sebuah pemikiran logis bahwa bahasa Toraja merupakan bahasa proto dari bahasa local lainnya seperti Makassar, Bugis dan Mandar. Penelitian ini bertujuan untuk mengetahui hubungan genetik antara bahasa Toraja dan bahasa Mandar dan untu mengidentifikasi perubahan bunyi dari bahasa Toraja dan bahasa Mandar. Penelitian ini menggunakan metode leksikostatistik dengan membandingkan 200 kata dasar Swadesh dari kedua bahasa tersebut. Hasil penelitian menujukkan bahwa bahasa Toraja dan bahasa Mandar dapat dikategorisasikan sebagai bahasa yang berkerabat dengan persentasi kemiripan sebesar 49% atau memiliki perbedaan sebesar 51% saja. Kedua, terdapat delapan jenis perubahan bunyi pada dua bahasa tersebut yakni syncope, lenition, fortition, assimilitaion, vowel breaking, metathesis dan prosthesis.